2017
DOI: 10.1111/wrr.12510
|View full text |Cite
|
Sign up to set email alerts
|

Topical application of nitrosonifedipine, a novel radical scavenger, ameliorates ischemic skin flap necrosis in a mouse model

Abstract: Ischemic skin flap necrosis can occur in random pattern flaps. An excess amount of reactive oxygen species is generated and causes necrosis in the ischemic tissue. Nitrosonifedipine (NO-NIF) has been demonstrated to possess potent radical scavenging ability. However, there has been no study on the effects of NO-NIF on ischemic skin flap necrosis. Therefore, they evaluated the potential of NO-NIF in ameliorating ischemic skin flap necrosis in a mouse model. A random pattern skin flap (1.0 × 3.0 cm) was elevated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 30 publications
(97 reference statements)
0
10
0
Order By: Relevance
“…While random-pattern skin flaps are convenient tools in tissue reconstruction, distal ischemic necrosis is a common clinical complication, limiting the use of random flaps and reducing the success of surgery 35,36 . The main reasons for ischemic necrosis at the distal flap are insufficient blood supply and ischemia-reperfusion injury 36,37 . Oxidative stress and apoptosis are two important mechanisms of ischemia-reperfusion injury, leading to further damage or necrosis of the tissue 38,39 .…”
Section: Discussionmentioning
confidence: 99%
“…While random-pattern skin flaps are convenient tools in tissue reconstruction, distal ischemic necrosis is a common clinical complication, limiting the use of random flaps and reducing the success of surgery 35,36 . The main reasons for ischemic necrosis at the distal flap are insufficient blood supply and ischemia-reperfusion injury 36,37 . Oxidative stress and apoptosis are two important mechanisms of ischemia-reperfusion injury, leading to further damage or necrosis of the tissue 38,39 .…”
Section: Discussionmentioning
confidence: 99%
“…Ischemia is a common complication following skin flap establishment, and with restoration of blood supply, tissue may undergo I/R injury. As a result, excess amounts of reactive oxygen species (ROS) is generated 32 . Trehalose has been reported to respond to high levels of ROS via regulating antioxidant gene expression and the autophagy pathway 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, random cutaneous flaps are frequently used in reconstructive surgery due to its simplicity, flexibility, and easy-of-use. However, since these flaps do not have specific blood vessels, there remains a risk of ischemia and necrosis 6 . Previous studies have shown that accelerating the angiogenesis in flaps is beneficial to improve the survival of flaps 7 , 8 .…”
Section: Introductionmentioning
confidence: 99%